KEPASTIAN HUKUM PELAKSANAAN EKSEKUSI PUTUSAN PIDANA YANG TELAH BERKEKUATAN HUKUM TETAP - Hidayat, Irfan (Jurnal HUKUM BISNIS, 2026)
The execution of criminal verdicts that have permanent legal force is a crucial stage in the criminal justice system, which serves to ensure legal certainty while upholding victims' rights. This research aims to examine the mechanism and procedure for the execution of final criminal verdict (inkracht van gewijsde). The execution of criminal verdicts is an important stage in the criminal justice system because it confirms the enforceability of court decisions while ensuring the achievement of legal certainty. In the context of criminal judgment execution, legal certainty not only protects the rights of victims and convicts but also reflects fair and effective law enforcement. In order for the execution to run in accordance with legal provisions, an in-depth understanding of the legal basis, formal procedures, and principles governing the rights and obligations of all parties involved is required. By using normative legal research methods as well as approaches based on laws and regulations and legal concepts, this study examines the mechanisms and procedures for the execution of criminal decisions that have permanent legal force. Keywords: Legal Certainty, Criminal Decision, Inkracht Van Gewijsde, Execution